Massive pulmonary tuberculosis cavity misdiagnosed as pneumothorax - Tam, John Kit-Chung (Blackwell Publishing Ltd, 2013)
Massive pulmonary cavity is a rare and serious complication of chronic reactivation tuberculosis. A 38-year-old gentleman had a history of tuberculosis treatment noncompliance 2 years ago. His presenting symptoms were cough, fever, and left-sided pleuritic chest discomfort for 2 months. Chest radiographs showed extensive lung destruction associated with large thick-walled cavities and severe fibrosis of the residual lung. In the emergency department, this was initially misdiagnosed as a large pneumothorax and a chest tube was inserted. Subsequently, this was misdiagnosed again as bronchopleural fistula when brisk air leak was seen. The chest tube did not lead to any radiological or clinical improvement and was removed without incident. This case demonstrates that massive pulmonary cavity can easily be misdiagnosed and tube thoracostomy is unnecessary. Although this condition was previously reported to be associated with a high mortality rate, our patient survived as a result of accurate diagnosis and prompt antituberculosis therapy.